Population biobanking in selected European countries and proposed model for a Polish national DNA bank - Sak, Jarosław (Springer-Verlag, 2012)
Population biobanks offer new opportunities for public health, are rudimentary for the development of its new branch called Public Health Genomics, and are important for translational research. This article presents organizational models of population biobanks in selected European countries. Review of bibliography and websites of European population biobanks (UK, Spain, Estonia). Some countries establish national genomic biobanks (DNA banks) in order to conduct research on new methods of prevention, diagnosis and treatment of the genetic and lifestyle diseases and on pharmacogenetic research. Individual countries have developed different organizational models of these institutions and specific legal regulations regarding various ways of obtaining genetic data from the inhabitants, donors’ rights, organizational and legal aspects. Population biobanks in European countries were funded in different manners. In light of these solutions, the authors discuss prospects of establishing a Polish national genomic biobank for research purpose. They propose the creation of such an institution based on the existing network of blood-donation centres and clinical biobanks in Poland.